Os sentidos das intervenções de terapeutas ocupacionais em saúde mental na perspectiva do sujeito das ações - Krutli, Renata Luiza dos Santos (Universidade Federal de São Carlos, 2024)
The usage of activities in the mental health field is not exclusive to occupational therapy; it is an extremely relevant resource in the psychosocial care practice which aims to create inclusive and emancipatory strategies of social participation. Studies show that occupational therapy is strong in its clinical and interdisciplinary work but has difficulties in affirming its own boundaries as a discipline. This work points to the need to better understand the practice of occupational therapy in the field of mental health alongside the subjects of health care actions; to identify how the occupational therapist is included in the lives of these subjects through their narratives; as well as valuing the perspective of these subjects on the processes that are experienced with the professionals. Therefore, this master’s thesis aimed to understand and analyze the life history of occupational therapy subjects in the field of mental health focusing on the meaning of these therapy processes and meetings according to the perspectives of these actors. This is qualitative study conducted using oral history as the method for data collection. The research participants were three attendees of an adult Psychosocial Care Center (CAPS III) in the city of São Paulo, SP, Brazil. The data was analyzed in two stages: the first focused on processing the interviews and textual construction following the guidelines of the oral history method; and the second focused on processing the data from the stories and coding them through Content Analysis. From the study of the thematic axis “Processes of care in occupational therapy,” regularities and discursive peculiarities were found and outlined three themes: 1. Life story; 2. Relationship with the CAPS; 3. Encounter with occupational therapy. Through the of themes “Life story” and “Relationship with the CAPS,” a lot was observed about the field of mental health in the Brazilian context and about the unique life trajectory of each participant in relation to the CAPS. The Care Center was described as a space for hospitality, listening, coexistence; but topics related to medical rationality, medicalization and the pathologization of life were brought up. In the theme “Encounter with occupational therapy”, the participants in this research brought the perspective of meeting someone who can take care of them. The meanings conveyed were related to a professional who encourages users to move forward in life, who provokes them, who uses tools to promote inclusion, who is willing to guarantee the subject's accessibility to their group and territory. Through the protagonism of the subjects who met with the occupational therapist, it was possible to understand the subjects' experiences with the occupational therapist and with occupational therapy. The participants in this research brought the perspective of their encounter with occupational therapy through the actions of the occupational therapist and from there it was possible to trace the framework, tools, and outlines of the professional core of occupational therapy that favored these encounters and the care offered to subjects.
The meanings of occupational therapists´ interventions in mental health from the perspective of the subject of the actions
Keywords: Terapia ocupacional; Saúde Mental; Sujeito; Equipe interprofissional; Atenção psicossocial; Occupational therapy; Mental health; Subject; Interprofessional team; Psychosocial care; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE